2021
DOI: 10.1002/adfm.202106835
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Transformation of a Core‐Shell Prussian Blue Analogue to a Bifunctional Electrocatalyst for Water Splitting

Abstract: Developing low‐cost oxygen evolution reaction (OER) catalysts with high efficiency and understanding the underlying reaction mechanism are critical for electrochemical conversion technologies. Here, an anodized Prussian blue analogue (PBA) containing Ni and Co is reported as a promising OER electrocatalyst in alkaline media. Detailed post‐mortem characterizations indicate the transformation from PBA to Ni(OH)2 during the anodic process, with the amorphous shell of the PBA facilitating the transformation by pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 62 publications
3
50
0
Order By: Relevance
“…01-0239) in XRD patterns ( Figure 1 e). In addition, the diffraction peaks shifted to a small angle as the proportion of Ni increased, indicating that the excess Ni atoms distorted the PBA lattice and formed the bimetallic NiFe PBA, which is consistent with the literature [ 17 ]. In addition to the fainter PBA diffraction peak of the NiFe 2-1/rGO material, a broader diffraction hump peak, which corresponds to the characteristic peak of graphite carbon, appears in the range of 15–27° [ 30 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…01-0239) in XRD patterns ( Figure 1 e). In addition, the diffraction peaks shifted to a small angle as the proportion of Ni increased, indicating that the excess Ni atoms distorted the PBA lattice and formed the bimetallic NiFe PBA, which is consistent with the literature [ 17 ]. In addition to the fainter PBA diffraction peak of the NiFe 2-1/rGO material, a broader diffraction hump peak, which corresponds to the characteristic peak of graphite carbon, appears in the range of 15–27° [ 30 ].…”
Section: Resultssupporting
confidence: 91%
“…PBAs have also been reported to be used directly as electrocatalysts. For example, D. Jason Riley et al used anodic oxidation to create NiCo@A-NiCo-PBA core-shell structure [ 17 ], while Zhu et al increased OH − adsorption at the reaction site by modulating the morphology and components of FeCoNi ternary PBA composites [ 18 ]. However, PBA has a poor charge transfer capacity, which restricts its intrinsic catalytic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that transition metal compounds exhibiting amorphous or poorly crystalline properties are more active than their crystalline counterparts. [ 30 , 33 , 34 ] The Fe 3 O 4 crystals are uniformly distributed on the NiC x pseudo‐amorphous substrates, and the lattice spacing of 0.219 nm and 0.257 mm corresponds to the (200) and (311) planes of Fe 3 O 4 . Scanning transmission electron microscopy‐energy dispersive X‐ray spectroscopy (STEM‐EDS; Figure 1l,m ) and STEM‐mapping (Figure 1n ) of NiFe‐PBA‐gel‐cal shows a uniform distribution of C, O, Ni, and Fe across the nanosheets, demonstrating the formation of Fe 3 O 4 on the pseudo‐amorphous NiC x .…”
Section: Resultsmentioning
confidence: 99%
“…[ 29 ] Prussian blue analogs (PBAs) are coordination frameworks with the advantages of adjustable cation composition and rich pore structure, which are good precursors for the preparation of TMOs and TMCs once calcined in appropriate atmospheres. [ 30 ] Most preparations of PBAs yield cubic crystalline structures, in which the exposed {100} surfaces are catalytically inert. [ 31 , 32 ] PBAs with a porous 2D network structure would possess more active sites and increased specific surface areas, greatly improving their catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 40–42 ] The sharp peaks at 656 and 563 cm −1 in the spectrum of Cl‐Co 3 O 4 ‐h are associated with Co II ‐Co III ‐O vibration in the tetrahedral hole and O‐Co III 3 vibration in the octahedral hole in the spinel lattice, respectively. [ 43,44 ] The analysis revealed the complete decomposition of the compound into Co 3 O 4 phase. The local coordination structures were characterized by FTIR.…”
Section: Resultsmentioning
confidence: 99%